2004
DOI: 10.1002/ijc.20178
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a complement regulator in vivo enhances antibody therapy in a model of mammary adenocarcinoma

Abstract: Key words: complement, Crry, inhibitor, antibody therapyComplement effector systems involved in an immune response to tumor cells can include the amplification of an inflammatory response, recruitment of immune effector cells, opsonization of tumor cells that result in complement-dependent cell-mediated cytotoxicity (CDCC) and enhanced antibody-dependent cell-mediated cytoxicity (ADCC), and direct complement mediated lysis. Normal and tumor cells are protected from complement by the expression of membrane boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…A previous proofof-principle study showed that the endogenous expression of Crry on a rat tumor cell line provided protection from mAb-mediated therapy. In this previous study, anti-rat Crry mAb was administered to immune-deficient mice challenged with rat tumor cells, thus allowing for tumor-specific targeting of rat Crry (49).…”
Section: Discussionmentioning
confidence: 99%
“…A previous proofof-principle study showed that the endogenous expression of Crry on a rat tumor cell line provided protection from mAb-mediated therapy. In this previous study, anti-rat Crry mAb was administered to immune-deficient mice challenged with rat tumor cells, thus allowing for tumor-specific targeting of rat Crry (49).…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been employed to target the overexpression of complement regulators and thereby improve the therapeutic outcome [34]. These include small interfering RNAs [35][36][37], neutralizing (blocking) mAbs to complement inhibitors [38,39], bispecific antibodies [40][41][42][43] and a targeted complement activator (CR2-Fc) [30,44].…”
Section: Cd46 As Tumor Targetmentioning
confidence: 99%
“…The complement-inhibitory activity of CR2-Crry and Crry-Ig was compared by measurement of the sensitivity of antibody-sensitized CHO cells to lysis by rat serum ( Figure 1B). Mouse Crry is functionally active against rat serum (45), and rat serum was used for functional comparison of activities because isolated mouse serum has poor lytic activity in vitro (46,47). CR2-Crry and Crry-Ig caused 50% inhibition of lysis at concentrations of 12 nM (0.84 μg/ml) and 40 nM (6.4 μg/ml), respectively, an approximately 3.5-fold difference.…”
Section: In Vitro Comparison Of Cr2-crry and Crry-igmentioning
confidence: 99%